THE EFFECT OF LIFE SKILL EDUCATION ON CIGARETTE CONTROL IN ADOLESCENTS - Umar Daeng Palallo (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Introduction : The World Health Organization (WHO) has warned that in the decade 2020-2030 tobacco will kill 10 million people per year, 70% of which occur in developing countries. The purpose of this study was to determine the smoking behavior of adolescents in the coastal area of Sinjai Regency and the factors related to smoking behavior in adolescents in the coastal area of Sinjai Regency. Method: this research use cross- sectional study. The study population was adolescents aged between 13-16 years as many as 231 people. The research sample of 50 people. The study was conducted in Pattongko Village, Tellulimpoe District, Sinjai Regency. The study was conducted October 1 - 28 2018, by monitoring smoking behavior in adolescents in coastal areas in Sinjai district. Result: The results of the study explained that the smoking behavior of adolescents based on frequent/high categories was 41 respondents (82%) and rarely/low was 9 respondents (18%); and health risks experienced by adolescents in the risk categories of 39 respondents (78%) and 11 respondents (22%). Adolescent smoking behavior in the frequent/high category that experiences a risk of 32 respondents (78.0) and no risk for 9 respondents (22.0%); while in the category of rare/low who experienced a risk of 7 respondents (77.8%) and no risk of 2 respondents (22.2%). Where the chi square test results of 0,000. Conclusion: That is, there is a relationship between smoking behavior with health risks experienced by adolescents.